ROLE OF THE TEACHER'S DISCUSSION SUBJECTS IN ENHANCING THE COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS - Saddam, Husein Sahrawi Saimima (al-Iltizam: Jurnal Pendidikan Agama Islam, 2019)
In education the various problems faced by teachers is still often the case, came successive as the development of the times. Ranging from lack of mastery of the material in the learning process, a lack of understanding on curriculum applied, stuttering in operating technology, often active on social media with things which are not educating which led to the loss of authority as a teacher and others. This paper uses qualitative research methods. Reasons to use qualitative research methods because the author wanted to describe the naturally muswarah on the role of teachers of subjects in improving teacher competence. Conclusion in this paper, the role MGMP in improving teacher competence Education of Islam among them as a forum, a. teacher competency through increased competence of pedagogic, social competence, personality, competencies, competency and professional, b. intellectual capacity building of teachers, c. as a discussion forum to find solutions in the face of challenges in the process of learning, d. increased sustainable profession forum.